Linear and nonlinear intraband optical properties of ZnO quantum dots embedded in SiO2 matrix - Deepti Maikhuri; S. P. Purohit; K. C. Mathur (AIP Advances, 2012)
In this work we investigate some optical properties of semiconductor ZnO spherical quantum dot embedded in an amorphous SiO2 dielectric matrix. Using the framework of effective mass approximation, we have studied intraband S-P, and P-D transitions in a singly charged spherical ZnO quantum dot. The optical properties are investigated in terms of the linear and nonlinear photoabsorption coefficient, the change in refractive index, and the third order nonlinear susceptibility and oscillator strengths. Using the parabolic confinement potential of electron in the dot these parameters are studied with the variation of the dot size, and the energy and intensity of incident radiation. The photoionization cross sections are also obtained for the different dot radii from the initial ground state of the dot. It is found that dot size, confinement potential, and incident radiation intensity affects intraband optical properties of the dot significantly.